Management research and the United Nations Sustainable Development Goals. (November 2020) - Macht, Stephanie A.; Chapman, Ross L.; Fitzgerald, Janna Anneke
Abstract: In this editorial, we are delighted to introduce the seven papers in this Special Issue. Each article considers various aspects of how management research can assist in the achievement of the United Nations Sustainable Development Goals (SDGs) in different contexts. Starting from a desire to provide a mechanism to drive real research outcomes for management research, this editorial considers the SDGs and their implementation/adoption in universities and businesses to date. It then introduces the different contexts for management research and the SDGs explored in the seven articles in the Special Issue. Finally, in a Postscript at the end of this Special Issue, we look at current progress against the SDGs, how COVID-19 has impacted this progress and what the future may hold for the links between management research and the SDGs.